Assessment of menstrual health among school going adolescent girls of urban slums of Berhampur, Odisha, India: a cross-sectional study - Mohanty, Sambedana; Panda, Manasee; Tripathi, Radha Madhab (International Journal Of Community Medicine And Public Health, 2016)
Background: Menarche is a significant milestone in the developmental journey of an adolescent girl about which she should be aware so that she can manage it properly. Poor personal hygiene and unhealthy menstrual practices give rise to repeated reproductive tract infections (RTIs). The Objectives were to assess the knowledge and perception regarding menarche; to study various problems related to menstruation and to evaluate various practices to manage menstruation with special emphasis on hygiene. Methods: Field based cross-sectional study was conducted among students of Class IX of a Government Girls High School in the field practice area of Department of Community Medicine in October 2015 using pre-designed, pre-tested, semi structured questionnaire. Data thus collected was analysed using appropriate statistics. Results: Menarche was attained by 86% of girls. Of which only 15% were aware about it. Mothers were the source of information for 94% of the girls. Duration of menstrual bleeding lasted normally for 3-4 days among 50% girls. Normal periodicity of cycles of (21-35) days was present in 69% of girls. Exclusively, sanitary napkins and clothes were used by 56% and 31% of the girls respectively. Clothes were reused by 73% of them, out of which 88% sundried after washing. Due to unavailability of soaps and dustbins, only 42% changed their pads or clothes in school. Conclusions: The knowledge and practice about menstruation is not adequate among the adolescent girls. Education of girls and their caretakers about healthy menstrual practices is essential .Schools should be provided with better sanitary facilities.